Clinical case report: considerable improvement of severe and difficult-to-treat obsessive-compulsive disorder with comorbid depression under treatment with esketamine and concomitant psychotherapy - Kaltenboeck, Alexander; Foerster, Elisa; Strafner, Sabrina; Demal, Ulrike; Mossaheb, Nilufar; Friedrich, Fabian (Frontiers in Psychiatry, 2023)
A 28-year-old man was admitted to our psychiatric ward with severe obsessive-compulsive disorder (OCD) and comorbid depression. At intake, obsessive-compulsive symptoms were present most time of the day and were related to an intense fear of causing interpersonal misunderstandings. Various treatment attempts, including cognitive-behavioural therapy (CBT) with exposure and response prevention (ERP), selective serotonin reuptake inhibitors, clomipramine, and add-on antipsychotics were either ineffective and/or were not tolerated, and the patient's condition worsened progressively. Following an in-depth multidisciplinary team discussion and a shared decision-making process, an off-label treatment trial with esketamine and concomitant psychotherapy was started. The patient received ten esketamine + psychotherapy sessions over a period of about 2 months, followed by two maintenance sessions in about 3-week intervals. After this, he was discharged into regular outpatient care where he continued to receive maintenance esketamine treatment every 4-6 weeks and, independent of this, individual CBT.Following the establishment of esketamine with concurrent psychotherapy, the patient exhibited a remarkable clinical improvement. Obsessive-compulsive symptoms showed a clear and sustained response (Y-BOCS before treatment > 35, Y-BOCS at week 8 = 23, Y-BOCS at week 26 = 14).Paralleling this, depressive symptoms also decreased (MADRS before treatment = 47, MADRS at week 9 = 12, MADRS at week 26 = 3). At a naturalistic follow-up at week 66, obsessive-compulsive symptoms were still mild (Y-BOCS = 13), and depression was still in remission (MADRS < 6). This clinical case suggests that (es)ketamine plus concomitant psychotherapy may hold promise as a therapeutic strategy for difficult-to-treat OCD and depression and its full clinical potential should be evaluated in more comprehensive future studies.